ACCESS TO PERSONAL ARCHIVES, A CONTRIBUTION TO CONTEMPORARY HISTORY: THE CASE OF JAIME GUZMAN’S ARCHIVE - Cofré Lagos, Benjamín Natanael (Revista de Historia Social y de las Mentalidades, 2020)
The Archival Science develops in ample spaces, as the national archives, but also in minor scales, going through big institutions, families, and not least, individuals and their private archives. This work proposes a theoretical revision of personal archives and its historiographic use as a source for the interpretation of Chilean History, with special interest in the contemporary History of the country. The article addresses the definition of this archives, its relation with History, also the access problems to its documentary collections and the role that archivists develop in these spaces, proposing as a case of study the Jaime Guzman’s Archive, a controversial person of interest to the national history.